Respuesta de temperatura y humedad relativa en el proceso de curación y secado de tabaco Burley - Gomez-Herrera, Edilson Daniel; Muñoz-Neira, Milton; Peñaranda-Mallungo, Luis Alfonso (Revista Científica, 2017)
This paper present the methodology development used for characterization and implementation of a control and automation of a camera for curing and drying of Burley tobacco, done with the purpose of analyzing its three stages: yellowing, color fixing and drying.As first step, the paper gives to know the process that is important for air curing of Burley tobacco. As second step, analysis of heating and humidification of system is presented, for determinate the most adequate control system for maintenance the ideal conditions for curing and drying of Burley. Results are presented through figures and tables.